The Effect of Using the “Find the Difference Game” Application on Improving Students’ Speaking Ability - Amalia, Inti Fada Putri (New Language Dimensions, 2023)
Speaking ability is one of the subjects that difficult to be mastered by young learners because of some problems. Describing picture strategy is one of the techniques that can be used by teachers to improve students' speaking ability. This research is used to find out whether using “Find the Difference Game” improve the speaking ability of 7th graders at Islamic junior high school. The 7th grader students of Islamic Junior high school in Pasuruan is the population of this study. To collect the data, this study uses test consist of pre-test and post-test. The data obtained were analyzed by using Wilcoxon test. The result of this research was the mean score obtained by the students through the pre-test and post-test from the experimental and control group. The experimental group has a pre-test score 30,83 and post-test score 50,63. While the control group has a pre-test score 30,62 and post-test score 46,46. The normality test result in this study shows that the data is not normal, so this study was using Wilcoxon test for testing the hypothesis. The Wilcoxon test result is Asymp.Sig (2-tailed) shows a score of 0.000. Since 0.000 is smaller than 0.05, it can be concluded that the hypothesis in this study is accepted. Therefore, hypothesis H0 was rejected and H1 was accepted. By this result, it can be concluded that by conducting describing picture strategy using “Find the Difference Game” can improve students’ speaking ability.